Leadership for SDG 6.2: Is Diversity Missing? - Kimberly Worsham; Ruth Sylvester; Georgia Hales; Kelsey McWilliams; Euphresia Luseka (SAGE Publishing, 2021)
Diversity, Equity, and Inclusion in the global sanitation sector have not been the subject of extensive investigation or scrutiny. However, without diverse leadership, the sector will continue to experience failure, inefficient use of dwindling resources, and overall low sanitation coverage rates, with 2 billion people lacking sanitation access. This research presents the first quantitative study of sanitation leadership demographics. The results revealed that older, white males from High-Income Countries comprised over a third of all leadership positions. This research found that two-thirds of all sanitation leaders were white, with white leaders 8.7 times more likely to hold multiple positions across different organizations than Black, Indigenous, or other People of Color. Eighty-eight out of one hundred organizations were headquartered in a High-Income Country, and western institutions dominated education data. Black, Indigenous, and other Women of Color were the least represented group, highlighting the importance of an intersectional perspective when discussing gender and racial equality. These issues must be urgently addressed if the Sustainable Development Goal 6.2 targets are to be met effectively. Institutional reform, inclusive hiring policies, and transforming individual attitudes are starting points for change. More organizational data should be made available, and further research needs to be conducted on these topics if a change is to be seen in time for 2030.